Determining photovoltaic array configurations with reduced impact of partial shading on energy performance - Shavolkin, Olexandr; Kruhliak, Hennadii; Shvedchykova, Iryna; Bila, Tetiana; Pisotskyi Andrіі (Eastern-European Journal of Enterprise Technologies, 2026)
This work explores energy processes in the array of photovoltaic panels within an object’s power supply system under dynamic modes of the partial-shading strip movement. The study aims to increase the energy productivity of a photovoltaic panel array in the power supply system at a local facility under partial shading conditions. Based on climatic data, the methodology for modelling the movement of a cloud shading strip, taking wind direction into account, has been substantiated. The array model has been improved by introducing a partial-shading strip that moves in specified directions. That has made it possible to assess the influence of strip direction and speed on dynamic modes for selected panel configurations, based on their location and connection topology. In accordance with the adopted array power, possible configurations with 16 photovoltaic panels, each of 655 W, have been determined. Modeling confirmed the complication of the trajectory of the global maximum power point under the conditions of shading strip movement. This manifests in the multiplicity of local maxima and in the unpredictable trajectory of the global maximum, which depends on the array configuration and the direction of strip movement. It was established that the strip speed did not affect the performance. According to the simulation results, recommended configurations with minimal shading impact on energy performance were obtained when the strip moved along the prevailing wind direction. It was shown that the generation power along the prevailing directions of the shading strip relative to the average value in all directions of movement is not less than 96%. The trajectory of the global maximum is monotonic, so no special algorithms are needed to track the maximum power. This makes it possible, at a panel power of 655 W, to form array configurations with a total power in the range of 3.93–15.72 kW.